URBAN CONSUMER ATTITUDE AND BEHAVIOR TOWARD TRADITIONAL HERBAL DRINKS (JAMU) CASE STUDY: MARKET PENETRATION STRATEGY FOR “RAMONA” PRODUCT (The Indonesian Journal of Business Administration, 2019)
There are so many companies unable to compete with other beverage products in our society today, especially in urban society. In the other hand, awareness of the dangerous impacts of chemicals in food is growing between people. The trend against purchasing organic food and drinks is increasing between people. As a basis for determining marketing strategies to increase sales it can be identified what encourages consumers to buy herbal drinks. Based on the planned behavior theory there are 3 main factors that affect behavioral intention: attitude towards behavior, subjective norms and perceived behavioral control. Attitude towards behavior includes health problems, environmental problems, product quality and marital status. This research have purpose to identify consumers' behavioral intention towards herbal drinks (jamu). This research showed that perceived behavioral control was the most influencing factor in behavioral intention, after that attitude and the last is subjective norms. These results are used as a reference for making a marketing mix strategy for PT Rahsa Nusantara for its new product, Ramona.Keywords:  urban consumer attitude and behavior, herbal drinks, marketing mix, market penetration strategy, planned behavior theory